Evaluación del efecto corrosivo de los crudos pesados sobre el Acero 5Cr-1/2Mo utilizado en las unidades de destilación - Darío Yesid Peña Ballesteros; Jose Anibal Serna; Raul Gonzalez (Revista Fuentes El Reventón Energético, 2008)
The heavy crude oil containing a high percentage of organic acids and sulfur, which at high temperatures and flow rates, resulting in corrosive furnaces, towers and lines transfer distillation units. The corrosive effect of two heavy crude oils with different TAN (number of total acidity) on stainless steel 5cr-1/2Mo, at three temperatures, maintaining a rotating speed and pressure constants were studied. The tests were conducted in a dynamic autoclave suitable for high temperature, by using gravimetric analysis to determine the corrosion rate. The dependence of the corrosion with the number of total acidity (TAN) and the content of sulfur compounds were evaluated. Subsequently, samples were characterized by SEM-EDX where sulfur compounds were found in the layer formed.